Tata Laksana Insomnia - Muhammad Abdul Ghoni Sutardi (Jurnal Medika Hutama, 2021)
Sleep is an important part of health and well-being. The harmful effects of insomnia, primary or secondary, are serious health concerns and should be examined and studied at all ages. There is growing evidence that the impact of insomnia on adolescent functioning is comparable to the effects of other major psychiatric disorders (eg mood disorders, anxiety disorders, etc.). Insomnia is associated with significant negative functional consequences and disability in many emotional, social, cognitive and physical domains. The purpose of this paper to determine tuberculosis therapy. The method used is literature research by searching for the words insomnia, therapy, pharmacology on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From the review that has been done, it is found that the pharmacotherapy given to insomnia patients is in the form of benzodiazepam and non-benzodiazepine-hypnotic drugs (zolpidem, eszoplocone, zaleplon ramelteon, trazodone).